Operation and installation of an industrial scale ethylene oxide plant using direct oxidation process a plant design - Reyes, Maria Angelica D.; Malimata, Jesselyn Rochelle R.; Tinguban, Grace Anne L.; Baynosa, Marjorie L.; Pajarito, Bryan B.; Rivera, Antonio Y. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Ethylene oxide (EO) is a widely used petrochemical compound derived from ethylene. Its major use it as a derivative to other chemicals like ethylene glycols, ethanolamines, and polymers. Final products include antifreeze agents, PET bottle resins, polyester films, aircraft and runway de-icing fluids, soaps and detergents, textile finishing, epoxy paints, and fumigants/sterilants. The goal of this plant design is to be able to fully design an ethylene oxide plant in the Philippines. Based on a previous market and feasibility study, it was concluded that the establishment of a Ethylene oxide plant in the Philippines will be profitable to future investors, and may help the country in the process of industrialization. A continuous direct oxidation over a catalyst was the proposed process for ethylene oxide production. The plant was proposed to be a part of a Chemical Park in Mati, Davao, in the Mindanao archipelago. This study aims to provide a more detailed design for the proposed plant and a more accurate economic analysis. First, the market study was briefly recapped to re-establish the relevance of designing an Ethylene oxide plant in the Philippines. The proposed sources of raw materials were then tabulated. Ethylene of 99.9 percent of purity will be obtained from a naphtha cracker within the proposed chemical park. Oxygen of 99.6% purity (0.4 percent Argon) will also obtained from a supplier inside the Chemical Park. Meanwhile, silver catalyst will be purchased from a third party. The proposed plant will have three sections: Section 100- Ethylene oxide Reactor, Section 200- Ethylene oxide Purification, and Section 300- Carbon Dioxide Recovery. The major equipment will be R-101, the Ethylene oxide Reactor in section 100. The major separation process will occur at E-204, the Ethylene oxide Refiner is section 200. The plant will have a total of 1 reactor, 6 towers, 9 heat exchangers, 5 vessels, 2 compressors, and 2 pumps. Safety, economics, and technical soundness were all considered in all designs. A Hazards and Operability (HAZOP) study was also done for the major equipment. Process controls including level control, temperature control, and pressure control were also included for each equipment design. The results of each design were specified in individual equipment specification and component specification sheets. A summary of all pertinent dimensions of the equipment was also tabulated. The proposed plant will be producing 160,000 metric tons of ethylene oxide and 56,000 MT/yr. Of carbon dioxide as a by-product at full capacity. This is comparable to the China exportation capacity of Thailand, our closest economy in Southeast Asia. The plant occupies a total land area of 70,000 square meters. Plant construction will be two years and will operate for the next 20 years. Production will be at 60 percent of the capacity in the first year, then 70 percent for the next year, and so on. It will reach its full capacity at 2019. The capital investment for the project is estimated at 157,000,000 US Dollar. The Internal Rate of Return is 17.89% with a payback period of 11 years. Based on the economic analysis done, it can be concluded that the proposed EO plant is feasible and profitable in its 20 years of operation.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Ethylene oxide; Chemical plants -- Design and construction